Fundo los Ulmos: a crossroad in the Chilean milk industry - Torres, Juan Pablo; Guidi Bresciani, Alexandra; Sanchez, Francisco (Estudios de Administración, 2020)
The case introduces the reader to the problems of a family business in the milk industry, Fundo Los Ulmos (FLU), which had to choose between two main alternatives to survive. The first option was to sell all the land belonging to the family business – a highly emotional situation for the person making the decision. The second option was to conduct an operational analysis intended to improve dairy management based on a model that optimizes milk production. This case highlights the typical problems of a family business where the decision-maker must deal with decisions that involve both analytical and socioemotional aspects. This case is especially relevant for determining competitive strategies in Latin American family businesses.